Reputation: 2387
I have the following differential equation : eq1
t = sp.Symbol("t")
f1=sp.Function("f1")(t)
f2=sp.Function("f2")(t)
eq1=sp.Eq(f1+f1.diff(t,2)-f2+f2.diff(t,1),0)
To move f2 terms from the lhs to the rhs, I used this code :
eq2=sp.Eq(eq1.lhs.subs(f2,0).doit(),eq1.lhs.subs(f1,0).doit()*-1)
Is it the right way to do that or is there a simpler solution ?
Thanks for answer.
Upvotes: 0
Views: 211
Reputation: 14500
That might fail if e.g. you have a 1/f1
somewhere. I'd do it like this:
In [18]: eq1
Out[18]:
2
d d
f₁(t) - f₂(t) + ───(f₁(t)) + ──(f₂(t)) = 0
2 dt
dt
In [19]: lhs, neg_rhs = (eq1.lhs - eq1.rhs).as_independent(f2, as_Add=True)
In [20]: eq2 = Eq(lhs, -neg_rhs)
In [21]: eq2
Out[21]:
2
d d
f₁(t) + ───(f₁(t)) = f₂(t) - ──(f₂(t))
2 dt
dt
https://docs.sympy.org/latest/modules/core.html#sympy.core.expr.Expr.as_independent
Upvotes: 2